1992
DOI: 10.1111/j.1464-410x.1992.tb15448.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Detrusor Innervation with Relief of Outflow Tract Obstruction

Abstract: In 10 patients with urodynamically proven outflow tract obstruction, detrusor biopsies were taken prior to and following relief of obstruction. The changes in detrusor innervation were compared following the relief of obstruction within the study group and also with an age-matched control group who were urodynamically normal. There was a significant reduction in detrusor innervation in the study group when compared with controls pre-operatively. Within the study group there was a significant increase in detrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 16 publications
0
28
0
3
Order By: Relevance
“…In the obstructed changes in both nerve and muscle. Supporting this idea is that the isoforms of lactate dehydrogenase are altered bladder the well documented changes in the density of innervation [4,9,10,12] suggest that there may therefore in unstable bladders, indicative of changes to cope with low oxygen tensions [8]. However, it is not known be an involvement of NGF.…”
Section: Muscle Hypertrophymentioning
confidence: 67%
See 1 more Smart Citation
“…In the obstructed changes in both nerve and muscle. Supporting this idea is that the isoforms of lactate dehydrogenase are altered bladder the well documented changes in the density of innervation [4,9,10,12] suggest that there may therefore in unstable bladders, indicative of changes to cope with low oxygen tensions [8]. However, it is not known be an involvement of NGF.…”
Section: Muscle Hypertrophymentioning
confidence: 67%
“…The mean the enzymes associated with metabolism [8]. In addition to the changes in muscle it has been reported that there (sd) ages of each group (normal, idiopathic and neuropathic) were 62 (9), 50 (11) and 31 (15) years, respectis a reduction in the density of motor nerves [9][10][11][12], which is associated with a decrease in the neuropeptide ively. None of the control group had received chemo-or radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment alternatives of OB include behavioural therapy, pelvic¯oor muscle training, antimuscarinic drugs, intravesical treatments, clean intermittent catheterisation, electrical nerve stimulation and, rarely, open surgery of the bladder. Surgery of the prostate can in some of these patients normalise the cystometric response in OB [Cumming and Chisholm, 1992;Chapple and Smith, 1994], and in others cause urge incontinence [Kimche et al, 1985;Staskin et al, 1988;Khan et al, 1991;Nitti et al, 1996]. Thus, decisions to perform surgery are not straightforward in these patients.…”
Section: Treatment Alternatives Of Obmentioning
confidence: 91%
“…Surgical relief of BOO obviously results in a recovery of normal detrusor behaviour in these patients [Cumming and Chisholm, 1992;Chapple and Smith, 1994]. In other subjects, a CNS disease or Fig.…”
Section: Development Of Obmentioning
confidence: 98%
“…65 A 56% reduction in the number of acetylcholine-positive nerves was demonstrated in bladder biopsies obtained from obstructed compared to nonobstructed men. 66 Counts of nerve profiles confirmed the reduced density of autonomic innervation and not merely a decrease in the concentration of AchE.…”
Section: Denervationmentioning
confidence: 88%